Pengembangan Kemampuan Penelitian Ilmiah dalam Rangka Membangun Kesadaran Tradisi Ilmiah di Perguruan Tinggi Islam - Khairunnisah Khairunnisah; Lalu Abdurrahman Wahid (AS-SABIQUN, 2022)
The development of scientific research in Islamic universities continues to be pursued by university managers. However, there are still obstacles and several other factors in the university space which still show that the university environment does not appear pro to research. This study aims to provide information related to the challenges and efforts of higher education institutions in increasing the awareness and ability of students and lecturers in carrying out scientific tradition activities at Islamic universities, especially related to awareness of conducting research and publishing scientific works.method library research The results of the study show that there are still serious problems related to the awareness and ability of scientific research in Islamic universities. several things that become obstacles and challenges for Islamic universities in creating a pro-research academic community, namely the weakness of the scientific community in conducting continuous and directed research, inadequate scientific research budgets, lack of awareness among the economic sector about the importance of scientific research, inadequate library facilities, documentation and information center, isolation of scientists and bureaucracy, restrictions and lack of incentives.